Analisis Respon Siswa Pada Pembelajaran Biologi Kelas X SMA Negeri 3 Siak Hulu - Citra Imanda Salsabilah; Ibnu Hajar (Universitas Palan, 2024)
This research is motivated by problems that arise in the learning process. This research aims to reveal students' responses to biology learning. The subjects of this research were students of SMAN 3 Siak Hulu. The research population was class X of SMAN 3 Siak Hulu, more specifically classes X4 and X5. The sample in this study consisted of 40 students from 2 different classes selected through random sampling techniques. The data collected is the result of distributing an online questionnaire using Google Form. The results of the research show that student learning motivation in biology subjects produces an average percentage of 95.4% with very good interpretation criteria.